VEGF protects brain against focal ischemia without increasing blood-brain permeability when administered intracerebroventricularly - (:unkn) unknown (SAGE PUBLICATIONS INC, 2005)
Delayed administration of vascular endothelial growth factor (VEGF) promotes functional recovery after focal cerebral ischemia. However, early intravenous injection of VEGF increases blood-brain barrier (BBB) leakage, hemorrhagic transformation and infarct volume whereas its application to cortical surface is neuroprotective. We have investigated whether or not early intracerebroventricular administration of VEGF could replicate the neuroprotective effect observed with topical application and the mechanism of action of this protection. Mice were subjected to 90 mins middle cerebral artery (MCA) occlusion and 24h of reperfusion. Vascular endothelial growth factor (8ng, intracerebroventricular) was administered 1 or 3h after reperfusion. Compared with the vehicle-treated (intracerebroventricular) group, VEGF decreased the infarct volume along with BBB leakage in both treatment groups. Neurologic disability scores improved in parallel to the changes in infarct volume. Independently of the decrease in infarct size, VEGF also reduced the number of TUNEL-positive apoptotic neurons. Phospo-Akt levels were significantly higher in ischemic hemispheres of the VEGF-treated mice. Contrary to intracerebroventricular route, intravenous administration of VEGF (15 mu g/kg) enhanced the infarct volume as previously reported for the rat. In conclusion, single intracerebroventricular injection of VEGF protects brain against ischemia without adversely affecting 131313 permeability, and has a relatively long therapeutic time window. This early neuroprotective action, observed well before recovery-promoting actions such as angiogenesis, possibly involves activation of the PI-3-Akt pathway.
Keywords: focal cerebral ischemia; neuronal apoptosis; neuroprotection; VEGF (vascular endothelial growth factor); ENDOTHELIAL GROWTH-FACTOR; CEREBRAL-ARTERY OCCLUSION; REDUCES INFARCT SIZE; NEUROTROPHIC FACTOR; GENE-EXPRESSION; NITRIC-OXIDE; RAT-BRAIN; HIPPOCAMPAL-NEURONS; TEMPORAL PROFILE; ANGIOGENESIS